2022
DOI: 10.3389/fnagi.2022.847315
|View full text |Cite
|
Sign up to set email alerts
|

Practice Effects in Mild Cognitive Impairment Increase Reversion Rates and Delay Detection of New Impairments

Abstract: ObjectiveCognitive practice effects (PEs) can delay detection of progression from cognitively unimpaired to mild cognitive impairment (MCI). They also reduce diagnostic accuracy as suggested by biomarker positivity data. Even among those who decline, PEs can mask steeper declines by inflating cognitive scores. Within MCI samples, PEs may increase reversion rates and thus impede detection of further impairment. Within an MCI sample at baseline, we evaluated how PEs impact prevalence, reversion rates, and dement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…Valid instruments and implementations of cognitive tests are essential for the evaluation of cognitive status, decline and subsequent dementia diagnosis, and the screening of at-risk participants for clinical trials and population intervention programs for dementia prevention. However, practice effects (PE) after repeated cognitive measurements, which refer to improvements in test performance due to repeated exposure to test materials or procedures ( Hausknecht et al, 2007 ; Goldberg et al, 2015 ), often mask a potential cognitive decline and remain a major issue in clinical and research settings ( Houx et al, 2002 ; Sanderson-Cimino et al, 2022 ). Failing to account for practice effects in cognitive tests could delay diagnosis and clinical care for patients with cognitive deficits.…”
Section: Introductionmentioning
confidence: 99%
“…Valid instruments and implementations of cognitive tests are essential for the evaluation of cognitive status, decline and subsequent dementia diagnosis, and the screening of at-risk participants for clinical trials and population intervention programs for dementia prevention. However, practice effects (PE) after repeated cognitive measurements, which refer to improvements in test performance due to repeated exposure to test materials or procedures ( Hausknecht et al, 2007 ; Goldberg et al, 2015 ), often mask a potential cognitive decline and remain a major issue in clinical and research settings ( Houx et al, 2002 ; Sanderson-Cimino et al, 2022 ). Failing to account for practice effects in cognitive tests could delay diagnosis and clinical care for patients with cognitive deficits.…”
Section: Introductionmentioning
confidence: 99%
“…A second limitation involves reversion due to practice effects. Our participants were followed until a reversion event occurred, exposing them to multiple testing sessions, potentially leading to practice effects that masked true decline [57]. Since we implemented an extensive test battery with a larger number of non-amnestic tests, the likelihood of finding non-amnestic MCI subjects is artificially high.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Using this method, it has been shown that adjusting for PEs leads to an earlier detection of MCI, improves stability of MCI diagnoses, and strengthens our ability to predict conversion to dementia (Sanderson-Cimino, Elman, Tu, Gross, Panizzon, Gustavson, Bondi, Edmonds, Eglit, et al, 2022; Sanderson-Cimino, Elman, Tu, Gross, Panizzon, Gustavson, Bondi, Edmonds, Eppig, et al, 2022). Failure to adjust for PEs also decreases statistical power and may have a substantial impact on the financial, staff, and patient burden of clinical drug trials that investigate conversation to MCI or dementia (Elman et al, 2018; Sanderson-Cimino, Elman, Tu, Gross, Panizzon, Gustavson, Bondi, Edmonds, Eglit, et al, 2022; Sanderson-Cimino, Elman, Tu, Gross, Panizzon, Gustavson, Bondi, Edmonds, Eppig, et al, 2022).…”
mentioning
confidence: 97%
“…Repeated assessments are subject to practice effects (PEs) that impair our ability to detect change. PEs can be defined as improvements in performance due to familiarity with testing rather than any actual alteration of true ability; put simply, someone taking a cognitive test for the second time often does better than if they were taking it for the first time (Calamia et al, 2012; Heilbronner et al, 2010; Salthouse, 2019; Sanderson-Cimino, Elman, Tu, Gross, Panizzon, Gustavson, Bondi, Edmonds, Eppig, et al, 2022). PEs are sometimes separated into content (i.e., knowledge of specific stimuli) and context (i.e., improved familiarity with testing, reduced anxiety) effects, although this delineation is somewhat heuristic (Gross et al, 2018; Heilbronner et al, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation